Symptomatic Pneumocephalus Associated with Lumbar Dural Tear and Reverse Trendelenburg Positioning: A Case Report and Review of the Literature - Stephen M. Pirris; Eric W. Nottmeier (Case Reports in Neurological Medicine)
Symptomatic pneumocephalus is a rare complication of degenerative lumbar spine surgery. This is a case report of a patient who developed transient diplopia associated with pneumocephalus following lumbar spine surgery complicated by a dural tear. The diplopia improved as the pneumocephalus resolved. Factors involved in the development of pneumocephalus include an unintended durotomy and intraoperative reverse Trendelenburg positioning that was utilized to decrease the risk of postoperative vision loss. When encountering cerebrospinal fluid (CSF) leakage intraoperatively, spine surgeons should level the operating table until closure of the dural defect to prevent potential complications associated with pneumocephalus. If postoperative patients complain of severe headaches or display a focal cranial neurologic deficit, then a computed tomography (CT) scan of the brain should be ordered and evaluated. Consulting neurologists should be aware of the circumstances surrounding this rare complication.